Formation of the methods and means of integrated mechanization cyclic lifting assembly and technological mobile komples (ATmK) - Chernenko, K. (Ways to Improve Construction Efficiency, 2015)
Presents the methods and features of formation of the foundations of a comprehensive mehanizatsii cyclical uplift MTmK gruzopodmnymi walking fashion-lyami in the construction of high-rise buildings.